1997
DOI: 10.1046/j.1464-410x.1997.00253.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing blood loss in transurethral resection of the prostate (TURP): auditing TURP

Abstract: Objectives  To assess the blood loss accompanying TURP and investigate its association with the resected weight of prostatic tissue, type of anaesthesia, type of presentation, histology, different surgeons and their differing techniques, and thus to reduce the morbidity associated with blood loss and transfusion. Patients and methods  All prostatectomies carried out in a district general hospital were audited prospectively, recording the pre‐ and post‐operative haemoglobin concentration (Hb), blood transfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 2 publications
4
16
0
2
Order By: Relevance
“…As such, SPUS shows promise as a modality to support modern surgical techniques like TURP for the management of BPH in sub-Saharan Africa. This study found a strong correlation (q = 0.98) between the preoperative volume of prostate using SPUS and TRUS, as in previous studies [5,7,8,[11][12][13][14]. Agreement between modalities was also strong, based on Bland-Altman analysis [10], with zero bias and upper and lower limits of agreement less than ±15 mL.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As such, SPUS shows promise as a modality to support modern surgical techniques like TURP for the management of BPH in sub-Saharan Africa. This study found a strong correlation (q = 0.98) between the preoperative volume of prostate using SPUS and TRUS, as in previous studies [5,7,8,[11][12][13][14]. Agreement between modalities was also strong, based on Bland-Altman analysis [10], with zero bias and upper and lower limits of agreement less than ±15 mL.…”
Section: Discussionsupporting
confidence: 86%
“…Differences between measurements are plotted against the mean of the measurements. The mean difference (bias) between volume of the enucleated adenoma and the preoperative prostate volume estimate was -12.5 and -12.4 mL for TRUS and SPUS, respectively studies found somewhat larger difference in means of prostate volume between SPUS and TRUS of 10 mL [12] and 8 mL [7], which might be explained by radiologist experience or patient characteristics. Preoperative assessment of prostate volume assists clinicians in assigning patients to TURP or to open prostatectomy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, transurethral resection of larger prostates is associated with a higher incidence of bleeding requiring transfusion, with the weight of resected tissue being the most important measureable factor in determining blood loss. 5 In one series, 85% of patients needed transfusion when resection exceeded 80 g of prostate. 6 Various prophylactic measures have been employed to reduce peri-operative bleeding including cessation of anticoagulant medical therapies such as aspirin products and warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…M. Kirollos and N. Campbell, 9 Jan Eken Gren, Robert G. Hahn 10 and Gordon 11 had not taken the factor for the study.…”
Section: Gland Size and Calculated Blood Lossmentioning
confidence: 99%